Maturing conditions of bimetallic nanocomposites as a new factor influencing Au–Ag synergism and impact of Cu(II) and/or Fe(III) on luminescence - Veronika Svačinová; Tomáš Pluháček; Martin Petr; Karolina Siskova (Royal Society Open Science)
Gold–silver synergism has been well documented in many scientific works dealing with luminescent nanostructures that are exploitable in biomedical and environmental application. Frequently, the ratio of Au : Ag in synthetic mixtures was varied to influence the extent of Au–Ag synergism of the resulting luminescent gold–silver nanoclusters (GSNCs). However, in our approach, a new step, maturing under differing conditions using the same Au : Ag ratio (5 : 1), has been investigated systematically for the very first time. As referent systems, monometallic gold nanoclusters (AuNCs) and protein treated by the conditions of synthesis and maturing were prepared and investigated. The selected types of maturing conditions led to distinct changes in fluorescence characteristics and, consequently, Au–Ag synergism extent (evaluated as the ratio of fluorescence quantum yields of GSNCs versus AuNCs). The best synergism was obtained for GSNCs matured at 37°C for 2.5 h. The stability of luminescent signal of these GSNCs was tested in the presence of an excess (to 20 mM) of Cu(II) and/or Fe(III) ions (crucial cofactors in living systems). The same metallic ion concentration caused different extents of GSNC luminescence quenching, for which a plausible reasoning is suggested.